When the Analytic Field Becomes a Minefield: Analyzing in the Post-9/11 Era. Issue 1 (31st December 2022) - Abbasi, Aisha
ABSTRACT: This paper addresses major changes that occurred in the analytic discourse between the author and her patients, following the catastrophe of 9/11. The author, an immigrant analyst, discusses new realizations she developed about herself during this period. She offers clinical examples to illustrate that an analyst's brutal honesty with herself, about difficult feelings that sometimes come to light as a result of external events, allows her analytic patients to reach parts of themselves that might otherwise have been kept concealed in the analysis.